The Prevalence Of Pulmonary And Cutaneous Manifestations In Connective Tissue Diseases: A Cross-Sectional Study (Journal of Pharmaceutical Negative Results, 2023)
Background: Connective tissue diseases (CTDs) are a group of disorders that affect the body’s connective tissues, including the skin, joints, and internal organs. Pulmonary and cutaneous manifestations are common in CTDs. The aim of this study was to determine the prevalence of pulmonary and cutaneous manifestations in CTDs.Methods: This cross-sectional study was conducted at the Pakistan Institute of Medical Sciences, Islamabad, Pakistan, between Jan 2022 to Jan 2023. A total of 100 patients with CTDs were included in the study. Data regarding sociodemographic characteristics, clinical manifestations, laboratory investigations, and chest radiography findings were collected.Results: The overall mean age of the patients was 42.4 ± 14.3 years. The most common CTD was systemic lupus erythematosus (SLE), followed by rheumatoid arthritis (RA). The most common pulmonary manifestation was dyspnea (54%), followed by pleuritic chest pain (50%). The most common cutaneous manifestation was discoid rash (68%), followed by photosensitivity (47%).Conclusions: Pulmonary and cutaneous manifestations are common in CTDs. Early diagnosis and timely management are essential to prevent the progression